Cost-effectiveness of endovascular thrombectomy for acute ischemic stroke with established large infarct in Germany: a decision tree and Markov model - Gottschalk, Sophie; König, Hans-Helmut; Subtil, Fabien; Bonekamp, Susanne; Denis, Angelique; Aamodt, Anne Hege; Fuentes, Blanca; Gizewski, Elke R; Hill, Michael D; Krajina, Antonin; Pierot, Laurent; Simonsen, Claus Ziegler; et al. (Journal of neurointerventional surgery, 2025)
BACKGROUND: Recent studies, including the TENSION trial, support the use of endovascular thrombectomy (EVT) in acute ischemic stroke with large infarct (Alberta Stroke Program Early Computed Tomography Score (ASPECTS) 3-5). OBJECTIVE: To evaluate the cost-effectiveness of EVT compared with best medical care (BMC) alone in this population from a German healthcare payer perspective. METHODS: A short-term decision tree and a long-term Markov model (lifetime horizon) were used to compare healthcare costs and quality-adjusted life years (QALYs) between EVT and BMC. The effectiveness of EVT was reflected by the 90-day modified Rankin Scale (mRS) outcome from the TENSION trial. QALYs were based on published mRS-specific health utilities (EQ-5D-3L indices). Long-term healthcare costs were calculated based on insurance data. Costs (reported in 2022 euros) and QALYs were discounted by 3% annually. Cost-effectiveness was assessed using incremental cost-effectiveness ratios (ICERs). Deterministic and probabilistic sensitivity analyses were performed to account for parameter uncertainties. RESULTS: Compared with BMC, EVT yielded higher lifetime incremental costs (€24 257) and effects (1.41 QALYs), resulting in an ICER of €17 158/QALY. The results were robust to parameter variation in sensitivity analyses (eg, 95% probability of cost-effectiveness was achieved at a willingness to pay of >€22 000/QALY). Subgroup analyses indicated that EVT was cost-effective for all ASPECTS subgroups. CONCLUSIONS: EVT for acute ischemic stroke with established large infarct is likely to be cost-effective compared with BMC, assuming that an additional investment of €17 158/QALY is deemed acceptable by the healthcare payer.
Keywords: senioři; rozhodovací stromy; analýza nákladů a výnosů; Quality-Adjusted Life Years; Thrombectomy; Stroke; Markov Chains; Economics; mužské pohlaví; ischemická cévní mozková příhoda; Cost-Benefit Analysis; Německo; trombektomie; Decision Trees; ženské pohlaví; Ischemic Stroke; Humans; kvalitativně upravené roky života; Germany; endovaskulární výkony; Endovascular Procedures; Female; Aged; Markovovy řetězce; lidé; Male